小線源治療による治療関連骨髄異形成症候群を発症後に晩期再発をきたした舌癌の1例 - 二宮, 嘉昭; 小川, 郁子; 武知, 正晃; 中川, 貴之; 植月, 亮; 太田, 耕司 (日本口腔外科学会雑誌, 2018)
We report a case of tongue cancer with late recurrence after the development of therapy-related myelodysplastic syndrome (t-MDS) induced by interstitial brachytherapy. The patient was a 40-year-old man. He recognized white patchy lesions on the right side of the tongue with ulcer formation and haphalgesia and visited our hospital in July 1997. An incisional biopsy was performed in January 1998, and the histopathological diagnosis was a moderately differentiated squamous cell carcinoma. Tongue cancer was diagnosed (T2N0M0) and the patient received interstitial brachytherapy (192 Ir, total 7,120 cGy). The tumor disappeared after the treatment. In January 2005, he presented to the department of hematology at our hospital with chronic anemia. He was given a diagnosis of t-MDS (refractory anemia) because of pancytopenia and bone marrow hypoplasia with normal karyotype. However, t-MDS of this patient was classified into the low risk group, and the patient underwent follow-up examinations regularly. In March 2014, 16 years after the interstitial brachytherapy, a recurrent lesion with erosion and induration was observed at the primary site of the tongue, and recurrent tongue cancer (rT4aN0M0) was diagnosed. Supraomohyoid neck dissection, subtotal glossectomy, and immediate reconstruction using a rectus abdominis flap were carried out. The postoperative course was uneventful for 3 years of follow-up, and no recurrence or metastasis has been noted since then.